2017
DOI: 10.1629/uksg.380
|View full text |Cite
|
Sign up to set email alerts
|

The role of the library in scholarly publishing: The University of Manchester experience

Abstract: The emergence of networked digital methods of scholarly dissemination has transformed the role of the academic library in the context of the research life cycle. It now plays an important role in the dissemination of research outputs (e.g. through repository management and gold open access publication processing) as well as more traditional acquisition and collection management. The University of Manchester Library and Manchester University Press have developed a strategic relationship to consider how they can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
3
4
0
Order By: Relevance
“…The review disclosed that libraries were offering research data support services such as analysis, publishing and visualization of research data to their users. These results are similar to those of previous studies (Bains, 2017; Borrego et al , 2018). Nowadays, libraries are considered to the primary research support service providers within organizations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The review disclosed that libraries were offering research data support services such as analysis, publishing and visualization of research data to their users. These results are similar to those of previous studies (Bains, 2017; Borrego et al , 2018). Nowadays, libraries are considered to the primary research support service providers within organizations.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, services related to the organization, dissemination and sharing of data were being provided to patrons. These results are also consistent with past literature (Bains, 2017; Daland, 2016; Todd and Kuhlthau, 2005) findings that had found that libraries offer such services (organization, dissemination and sharing of data). Hence, it can be maintained that role of libraries as research support department cannot be ignored.…”
Section: Discussionsupporting
confidence: 93%
“…Another feature in the development of DLP is its business model, which does not concentrate on making a profit (Bains, 2017;Raju & Pietersen, 2017;Skinner, Lippincott, Sper, & Walters, 2014). This was evident in the description of the publishing services offered at the Virginia Technical Libraries: "Library publishing services are free" (McMillan & Lawrence, 2013, p. 28).…”
Section: Growth Of Library Publishing Servicesmentioning
confidence: 99%
“…For the purposes of our study, we defined DLP as a set of activities conducted by college and university libraries to support institutional communities in developing, managing, and distributing online publications, including journals, conference materials, monographs, and other scholarly content. DLP services help scholars share their research through new and emerging publishing models in a constantly changing academic communication environment, and help control and solve the problems and issues related to electronic publishing (Bains, 2017;Ginther, Lackner, & Kaier, 2017;Raju, & Pietersen, 2017;Tracy, 2017). This trend becomes evident when examining how localized digital publishing services are in high demand by researchers in the United States (USA), Canada, Australia, Germany, the United Kingdom, Austria, Sweden and other countries (Bonn, & Furlough, 2015;Depping, 2014;).…”
Section: Introductionmentioning
confidence: 99%
“…Libraries in the age of transition to the digital economy and digital society are often pioneers in their universities in organizing and implementing digital scholarly and educational communication initiatives. Deciding to strengthen their position at universities, they are not afraid to experiment, challenge the status quo, and launch new services to meet the needs of new users and new strategies for developing their institutions (Bains, 2017;Kolesnykova & Matveyeva, 2019). The international editorial board appreciates the contribution of each author.…”
mentioning
confidence: 99%